The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s40001-015-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased in-hospital mortality following severe head injury in young children: results from a nationwide trauma registry

Abstract: BackgroundIn the current literature, the outcome of paediatric brain injury is controversially discussed. According to the majority of the studies, there seems to be a decreased mortality but worse recovery in paediatric, traumatic brain injury in comparison with adults. However, there is a lack of information concerning the differences in various stages of development in patients younger than 18 years. The aim of our study was to verify the in-hospital outcome of different paediatric age groups in comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
13
0
2
Order By: Relevance
“…This study identifies the predictors of mortality in school-aged children with severe TBI, which are focused on less in current literature [ 11 , 36 ]. Our results showed that approximately 25% of school-aged children with TBI arrived at the ED with severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…This study identifies the predictors of mortality in school-aged children with severe TBI, which are focused on less in current literature [ 11 , 36 ]. Our results showed that approximately 25% of school-aged children with TBI arrived at the ED with severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that a lower GCS score was significantly related to fatality and injury with a maximum AIS score ≥3, and a higher head AIS score was significantly related to fatality. Traumatic head injury is the leading cause of mortality and disability in children and adolescents [28][29][30][31]. A retrospective study in Australia showed that having a head injury and greater injury severity were associated with a higher mortality rate [32].…”
Section: Discussionmentioning
confidence: 99%
“…A previous nationwide Japanese analysis that focused on patients’ age-related characteristics showed that, among younger paediatric patients with severe injury, especially those <10 years, the proportion of those with traumatic head injury was higher than that of the other patients [ 16 ]. Furthermore, traumatic head injury is a leading cause of mortality and disability among children and adolescents [ 19 , 20 , 21 , 22 ]. Our multivariate logistic regression analysis also showed higher odds of in-hospital mortality among those with higher injury severity.…”
Section: Discussionmentioning
confidence: 99%